Laboratório virtual de minirredes de energia elétrica com geração distribuída - RAMOS, Vanessa Menezes (2018)
This study approaches the development of a computational tool in LabVIEW environment, called Virtual MicroGrid Laboratory where it is possible actuation the switches and the monitoring of electrical variables at different points of a microgrid of power generation with hybrid features installed in area belonging to the Group of Studies and Development of Energy Alternatives (GEDAE), the Federal University of Pará, on the campus of Belém. The developed tool has the communication function with transducers of electrical and Programmable Logic Controllers (PLC’s) aimed at opening and closing contactors switches resulting in different settings for the microgrid, also based on the proposed configuration can be displayed in real time and stored data obtained. The study also describes the implanted microgrid in GEDAE and its components (facilities, generation systems and loads proposals) and presents the materials and methods used for the preliminary development of the Virtual Laboratory. In order to contextualize the study, are also covered concepts microgrid, with greater emphasis on the power grid distribution considered as Smart Grid.